2008
DOI: 10.1111/j.1745-7599.2008.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing nurse practitioner practice by sampling patient encounters: An APRNet study

Abstract: Despite many studies on the comparability and outcomes of NP practice, the need to identify, clarify, and document the practices of NPs in primary care settings remains. The present survey provides an important and useful first step in providing a systematic way to characterize these practices through a survey of APRNs immediately following their patient encounters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…It has been found that a higher proportion of “nonphysician clinicians” care for individuals who are uninsured and underserved (Brown, 2007; Grumbach, Hart, Mertz, Coffman, & Palazzo, 2003). Advanced practice nurses (APNs) routinely see a substantial number of clients who have no health insurance or receive government assistance for healthcare services (Deshefy‐Longhi, Swartz, & Grey, 2008; Goolsby, 2005; Swartz, Grey, Allan, Ridenour, Kovner, Walker, et al, 2003). Additionally, NMHCs provide improved access to quality primary care where previously few or no services were available (Clear, Starbecker, & Kelly, 1999).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It has been found that a higher proportion of “nonphysician clinicians” care for individuals who are uninsured and underserved (Brown, 2007; Grumbach, Hart, Mertz, Coffman, & Palazzo, 2003). Advanced practice nurses (APNs) routinely see a substantial number of clients who have no health insurance or receive government assistance for healthcare services (Deshefy‐Longhi, Swartz, & Grey, 2008; Goolsby, 2005; Swartz, Grey, Allan, Ridenour, Kovner, Walker, et al, 2003). Additionally, NMHCs provide improved access to quality primary care where previously few or no services were available (Clear, Starbecker, & Kelly, 1999).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…6 Unfortunately, most efforts at defining advanced practice nursing and the NP workforce have focused on the care of adults or have included children only in the overall health care workforce needs of the entire population. [7][8][9] Because children constitute a decreasing proportion of the US population, such studies are not truly applicable to pediatric care. 10 The pediatric health care delivery system in this country often functions with a different set of parameters, workforce constraints, and financing and delivery systems.…”
mentioning
confidence: 99%
“…3,4 In 2009, researchers and clinicians partnered in the Athletic Training PBRN (AT-PBRN) to develop an infrastructure for engaging in multisite clinical research aimed at enhancing patient care and improving patient outcomes. The AT-PBRN first received recognition as a registered affiliate PBRN from the Agency for Healthcare Research and Quality (AHRQ) in January 2010 and is the first PBRN in the athletic training profession.…”
mentioning
confidence: 99%